Γ-Glutamyl valine supplementation-induced mitigation of gut inflammation in a porcine model of colitis. (June 2016) - Zhang, Hua; Kodera, Tomohiro; Eto, Yuzuru; Mine, Yoshinori
Highlights: Dietary dipeptide γ-glutamyl valine is an effective anti-inflammatory agent. Maintaining epithelial architecture and barrier function in porcine colitis model. Attenuating local inflammation and potentially restoring immune homeostasis. Abstract: A dietary peptide γ-glutamyl valine (EV) possesses the agonistic property to activate a calcium-sensing receptor-mediated anti-inflammatory pathway, thereby suppressing inflammation. This study aims to substantiate the therapeutic efficacy of γ-EV as an anti-inflammatory agent in a dextran sodium sulphate (DSS)-induced colitis porcine model. Colitis symptoms were observed after intra-gastric infusion of DSS for five days, followed by five days of administration of saline or γ-EV. γ-EV supplementation reduced DSS-induced weight loss and clinical signs, while preserving colonic architecture and intestinal permeability. Colonic production of tumour necrosis factor (TNF)-α and interleukin (IL)-6 were reduced to a level observed in animals without DSS treatment. The colonic gene expression of TNF-α, IL-6, IL-1β and interferon (IFN)-γ were also mitigated by γ-EV treatment, thus indicating γ-EV can restore immune homeostasis by attenuating inflammation. Our findings suggest that γ-EV supplementation may be a promising therapeutic strategy in the treatment of intestinal inflammation.